2005
DOI: 10.1124/mol.105.015255
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Stromal Cell-Derived Factor 1α Induces Proliferation and Growth Hormone Release in GH4C1 Rat Pituitary Adenoma Cell Line through Multiple Intracellular Signals

Abstract: We used GH4C1 cells as a model to study the effects of the chemokine stromal cell-derived factor 1 (SDF1) in pituitary functions. In these cells, SDF1␣ induced proliferation and growth hormone secretion, suggesting a possible regulatory role for this chemokine at pituitary level. We evaluated the intracellular signaling involved in these effects: SDF1␣ increased cytosolic [Ca 2ϩ ] and activated Pyk2, extracellular signal-regulated kinases 1 and 2 (ERK1/2), and large-conductance Ca 2ϩ -activated K ϩ channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…These data indicate that SDF1 activity requires the activation of a G-protein of the Gi/Go subfamily, and that its effects are responsive to inhibitory stimuli as observed in both normal pituitary and secreting adenomas. Interestingly, pertussis toxin was able to abolish both the stimulatory effects of SDF1 (Florio et al 2006) and the inhibitory effects of somatostatin (Florio & Schettini 1996). SDF1 was also a powerful mitogen for GH4C1 cells, with a statistically significant effect already evident at a concentration of 6 .…”
Section: Biological Effects Of Sdf1 In Pituitary Adenoma Cells: the Gmentioning
confidence: 95%
See 2 more Smart Citations
“…These data indicate that SDF1 activity requires the activation of a G-protein of the Gi/Go subfamily, and that its effects are responsive to inhibitory stimuli as observed in both normal pituitary and secreting adenomas. Interestingly, pertussis toxin was able to abolish both the stimulatory effects of SDF1 (Florio et al 2006) and the inhibitory effects of somatostatin (Florio & Schettini 1996). SDF1 was also a powerful mitogen for GH4C1 cells, with a statistically significant effect already evident at a concentration of 6 .…”
Section: Biological Effects Of Sdf1 In Pituitary Adenoma Cells: the Gmentioning
confidence: 95%
“…We used GH4C1 cells to evaluate the intracellular mechanisms activated by SDF1 to induce hormone release and cell proliferation (Florio et al 2006). We analyzed a set of intracellular mediators that were previously involved in CXCR4 effects, namely the regulation of the intracellular Ca CC concentration, the activation of ERK1/2 and of the cytosolic Ca CC -dependent tyrosine kinase, Pyk2, and the stimulation of the large conductance, Ca CC -activated K C channels BK Ca .…”
Section: Intracellular Mechanisms Involved In Sdf1 Regulation Of Gh4cmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, it was also observed that CINC stimulates adrenocorticotrophin but not thyrotrophin secretion and that CINC suppresses the basal luteinizing hormone (LH) and follicle stimulating hormone (FSH) secretions from normal anterior pituitary cells in a dose-dependent manner (Sawada et al 1994). Moreover, a recent study shows that CXCR4 mRNA is expressed in the rat pituitary adenoma cell line GH4C1 (a cell line that releases growth hormone) and that SDF-1a/CXCL12 causes both proliferation and growth hormone release, suggesting that the activation of CXCR4 may represent a novel regulatory mechanism for growth hormone secretion and pituitary cell proliferation, which may contribute to pituitary adenoma development (Florio et al 2006). .…”
Section: Chemokines and Pituitary Hormonesmentioning
confidence: 99%
“…Transient Ca 2+ elevation is an important consequence of ligand-induced chemokine receptor activation (Boutet A et al, 2001;Gillard SE et al, 2002). Binding of CXCL12 to CXCR4 also induces the activation of phosphoinositide-3 kinase (PI3K) that activates downstream AKT, PyK2 and nuclear transcriptional factor NF κ B signaling pathways (Bajetto A et al, 2001;Han Y et al, 2001a;Fernandis AZ et al, 2004;Lee BC et al, 2004;Alvarez S et al, 2005;Kukreja P et al, 2005;Florio T et al, 2006). G-protein dependent activation of CXCR4 also induces several MAPKs signaling pathways such as ERK, JNK and P38 (Bajetto A et al, 2001;Han Y et al, 2001a;Han Y et al, 2001b;Fernandis AZ et al, 2004;Alvarez S et al, 2005).…”
Section: Cxcl12/cxcr4 Signaling Pathwaysmentioning
confidence: 99%